Experiences of neurodivergent students in graduate STEM programs - Syharat, Connie Mosher; Hain, Alexandra; Zaghi, Arash E.; Gabriel, Rachael; Berdanier, Catherine G. P. (Frontiers in Psychology, 2023)
This qualitative study presents a novel model for understanding the experiences of neurodivergent graduate students in STEM programs. We used thematic analysis of transcripts from 10 focus group sessions to examine the experiences of 18 students who identify as neurodivergent in graduate STEM programs at a large, research-intensive (R1) university. In this analysis, we consider how common graduate school experiences interface with the invisibility of neurological diversity, thus contributing to a set of unique challenges experienced by neurodivergent students. The findings suggest that students who identify as neurodivergent feel pressure to conform to perceived neurotypical norms to avoid negative perceptions. They also may self-silence to maintain stability within the advisor-advisee relationship. The stigma associated with disability labels contributes a heavy cognitive and emotional load as students work to mask neurodiversity-related traits, navigate decisions about disclosure of their neurodivergence, and ultimately, experience significant mental health challenges and burnout. The findings presented through this novel model of neurodivergent graduate STEM student experiences may have implications for current and future graduate students, for graduate advisors who may or may not be aware of their students’ neurodivergence, and for program administrators who influence policies that impact the wellbeing and productivity of neurodivergent students.